2021
DOI: 10.1038/s41467-021-22536-y
|View full text |Cite
|
Sign up to set email alerts
|

Cell barrier function of resident peritoneal macrophages in post-operative adhesions

Abstract: Post-operative adhesions are a leading cause of abdominal surgery-associated morbidity. Exposed fibrin clots on the damaged peritoneum, in which the mesothelial barrier is disrupted, readily adhere to surrounding tissues, resulting in adhesion formation. Here we show that resident F4/80HighCD206− peritoneal macrophages promptly accumulate on the lesion and form a ‘macrophage barrier’ to shield fibrin clots in place of the lost mesothelium in mice. Depletion of this macrophage subset or blockage of CD11b impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 55 publications
2
26
0
Order By: Relevance
“…Changes in macrophage dynamics, in particular the loss of F4/80 high cavity resident macrophages after surgery, has previously been reported with C57BL/6 mice ( 25 ). However, specific differences between BALB/c and C57BL/6 mice have not been investigated; hence we performed a more in-depth characterization of the dynamic changes in peritoneal macrophage subsets following surgery in the two strains.…”
Section: Resultssupporting
confidence: 58%
“…Changes in macrophage dynamics, in particular the loss of F4/80 high cavity resident macrophages after surgery, has previously been reported with C57BL/6 mice ( 25 ). However, specific differences between BALB/c and C57BL/6 mice have not been investigated; hence we performed a more in-depth characterization of the dynamic changes in peritoneal macrophage subsets following surgery in the two strains.…”
Section: Resultssupporting
confidence: 58%
“…Much of the transcriptional and functional behaviour of cavity macrophages is driven by retinoid X receptors and the transcription factor GATA6 in response to local production of the vitamin A metabolite retinoic acid [6][7][8][9]. Despite playing key roles in many peritoneal diseases [1,[10][11][12][13] our understanding of the cellular interactions that regulate the identity and maintenance of these macrophages remains incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in macrophage dynamics, in particular the loss of F4/80 high cavity resident macrophages after surgery, has previously been reported with C57BL/6 mice [24]. However, specific differences between BALB/c and C57BL/6 mice have not been investigated; hence we performed a more in-depth characterisation of dynamic changes in peritoneal macrophage subsets following surgery in the two strains.…”
Section: Resultsmentioning
confidence: 90%
“…Similarly, two recent studies suggested that rapid recruitment of F4/80 high peritoneal resident macrophages to the site of mesothelial injury may result in the creation of a barrier preventing excessive fibrin attachment and consequently preventing the formation of adhesions after surgery (25, 35). We found that C57BL/6 mice showed a significantly higher number of peritoneal F4/80 high resident macrophages prior and at day 3 post-surgery compared with BALB/c mice.…”
Section: Discussionmentioning
confidence: 99%